COVID-19–associated mucormycosis: Evidence-based critical review of an emerging infection burden during the pandemic’s second wave in India - Jesil Mathew Aranjani (Public Library of Science (PLoS), 2021)
Coronavirus Disease 2019 (COVID-19), during the second wave in early 2021, has caused devastating chaos in India. As daily infection rates rise alarmingly, the number of severe cases has increased dramatically. The country has encountered health infrastructure inadequacy and excessive demand for hospital beds, drugs, vaccines, and oxygen. Adding more burden to such a challenging situation, mucormycosis, an invasive fungal infection, has seen a sudden surge in patients with COVID-19. The rhino-orbital-cerebral form is the most common type observed. In particular, approximately three-fourths of them had diabetes as predisposing comorbidity and received corticosteroids to treat COVID-19. Possible mechanisms may involve immune and inflammatory processes. Diabetes, when coupled with COVID-19–induced systemic immune change, tends to cause decreased immunity and an increased risk of secondary infections. Since comprehensive data on this fatal opportunistic infection are evolving against the backdrop of a major pandemic, prevention strategies primarily involve managing comorbid conditions in high-risk groups. The recommended treatment strategies primarily included surgical debridement and antifungal therapy using Amphotericin B and selected azoles. Several India-centric clinical guidelines have emerged to rightly diagnose the infection, characterise the clinical presentation, understand the pathogenesis involved, and track the disease course. Code Mucor is the most comprehensive one, which proposes a simple but reliable staging system for the rhino-orbital-cerebral form. A staging system has recently been proposed, and a dedicated registry has been started. In this critical review, we extensively analyse recent evidence and guidance on COVID-19–associated mucormycosis in India.